Analisis Aplikasi Kredivo Berdasarkan Information System Success Model (ISSM) - Abidin Abidin; Abdul Yusuf; Novia Syafa’a Zahra (Jurnal Maksipreneur, 2023)
In this digital era, the implementation of information systems in various areas of life continues to increase. Information system implementations need to be evaluated for their success. Delone and Mclean have developed an information system success model as a framework for measuring the success level of information systems. The purpose of this research is to conduct a thorough analysis, increase knowledge regarding the ISS Model, and find out its relevance as a research basis on the Kredivo FinTech platform. Of the several variables included in the ISSM, the results of this study indicate that only the user satisfaction has a significant effect on net benefits.